2014
DOI: 10.14260/jemds/2014/3956
|View full text |Cite
|
Sign up to set email alerts
|

An Osteological Study of Foramen Trasversarium: Variations and Clinical Aspects

Abstract: Foramen transversarium are located on the transverse process of cervical vertebrae and are the cardinal features of cervical vertebrae. These foramina are known to exhibit variations in size, shape and may be absent or duplicated. Keeping this in mind, a study was done to record these variations. A hundred and twenty dry typical cervical vertebrae procured from department of anatomy were used for this study. Unilateral double foramen transversarium were seen in 2.5% cases while 4.16% cases showed bilateral dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…In our study, the incidences of bilateral and unilateral FT were found as 14.6% and 7.3% respectively. Contrary to Yadav et al (18), bilateral double FT was observed to be more incident in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, the incidences of bilateral and unilateral FT were found as 14.6% and 7.3% respectively. Contrary to Yadav et al (18), bilateral double FT was observed to be more incident in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…These variations in FT may affect the anatomic progress of vital vascular and neurological structures and hence lead to pathological conditions. Yadav et al (18) report unilateral complete FT as 2.5%, bilateral complete FT as 4.16%, incomplete FT as 1.66%, and asymmetrical FT as 0.83%. In our study, unilateral complete FT was found as 7.3%, bilateral complete FT as 3.16%, incomplete FT as 16.9%, and asymmetrical FT as 1.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 (3%) cases of double FT was reported by Katikireddi RS et al 15 after study of 100 cervical vertebrae, in which 2 were unilateral & 1 was bilateral. Yadav Y et al 16 got only 8 (6.67%) cases of double FT among 120 cervical vertebrae, in which 3 were unilateral & 5 were bilateral. A single sixth cervical vertebra with bilateral double foramen FT with non-bifid spine was reported by Mishra GP et al 17 Double foramen transversarium is also known as "foramen transversarium bipartitia".…”
Section: Resultsmentioning
confidence: 96%
“…Different terminologies were used by many authors that reported varying number, shape and laterality of FT (Akhtar et al, 2015;Dofe et al;Gujar et al, 2015;Sabnis;Sangari et al, 2015;Esakkiammal & Chauhan, 2016;Molinet et al, 2017). Studies have displayed three complete FT present on a vertebra, with one on one side and two on the other-these have been termed unilateral complete double (accessory) FT (Murlimanju et al, 2011;Karau & Odula;Ramachandran et al;Yadav et al, 2014;Akhtar et al;Sangari et al;Esakkiammal & Chauhan;Molinet et al). Murlimanju et al and Rathnakar et al (2013) also found triple FT unilaterally on a typical cervical vertebra.…”
Section: Introductionmentioning
confidence: 99%